Morbidity and mortality weekly report, Vol. 6, no. 27, For release July 12, 1957 - United States Dept. of Health, Education, and Welfare Public Health Service; United States National Office of Vital Statistics
Provisional information on selected notifiable diseases in the United States and on deaths in selected cities for week ended July 6, 1957 -- Number of deaths in 114 selected cities -- Quarantine measures, Immunization information for international travel Epidemiological reports: Mortality -- Poliomyelitis in vaccinated persons -- Influenza -- Gastro-enteritis -- Encephalomyelitis in horses -- Communicable diseases in other areas Table 1. Cases of specified notifiable diseases: continental United States -- Table 2. Cases of specified notifiable diseases: United States, each division and state, Alaska, Hawaii, and Puerto Rico for weeks ended July 7, 1956 and July 6, 1957 -- Table 3. Deaths in selected cities by geographic division -- Table 4. Deaths in selected cities